Hubungan antara Peran Teman Sebaya dengan Pengetahuan Seksual Remaja di Sekolah Menengah Pertama - Anisa Septi Artanti; Rida Yanna Primanita (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the relationship between the role of peers and the sexual knowledge of junior high school (SMP) students in Batusangkar. The study employed a quantitative approach with a correlational design. The sample consisted of 120 students in grades 7–9, aged 13–15 years, selected using purposive sampling. The research instruments included a peer group scale developed based on Shaffer’s (1994) theory and a sexual knowledge scale based on Reinisch and Beasley’s (1990) theory. Data analysis utilized the Spearman Rank correlation test. The results indicated a very strong positive relationship between the role of peers and adolescents’ sexual knowledge (r = 0.844; p < 0.05). Based on these findings, it can be concluded that peers play a significant role in sexual knowledge. These results underscore the importance of peers as a significant source of information for adolescents in understanding sexual issues. Furthermore, the findings of this study are expected to serve as a foundation for developing more effective sexual education programs tailored to the needs of adolescents in junior high schools.